Exploration for Byproduct Critical Element Resources: Proxy Development Using a LA–ICP–MS Database - McNulty, Brian A.; Jowitt, Simon M. (Frontiers in Earth Science, 2022)
The transition towards zero-CO2 energy generation, storage and transport will require a range of metals that are often considered critical and are produced as byproducts of the production of other metals. This means that the reliance of some critical elements on the production of main metal commodities, such as Cu and Ni, is a significant source of supply risk. However, how can we evaluate resource scarcity and supply risks for elements that we do not routinely analyze for and characterize in present day mined ores? Here we demonstrate a method for exploring for and assessing the byproduct critical element potential of magmatic sulfide and volcanogenic massive sulfide deposits using a LA–ICP–MS database. Our results indicate there are significant enrichments of Sb, Bi, Cd, Co, Se and Te in pentlandite (Ni sulfide), chalcopyrite (Cu sulfide) and sphalerite (Zn sulfide) within these systems, demonstrating the need for a holistic approach to critical element research with unrecovered byproducts in existing mining supply chains having the potential to solve perceived resource scarcity challenges.